The prevalence of Trichuris spp. infection in indoor and outdoor cats on St. Kitts - Jenifer Kathleen Ketzis; Linda Shell; Sarah Chinault; Charles Pemberton; Mary M Pereira (Journal of Infection in Developing Countries)
Introduction: The present study was conducted to evaluate the prevalence of Trichuris spp. and other intestinal parasitic infections in owned cats on St. Kitts. Methodology: The feces of 41 non-feral cats (23 indoor only; 18 indoor/outdoor) were examined for the presence of Trichuris spp. eggs. Results: Nine (22%) of the cats were positive for Trichuris spp. Prevalence of trichuriasis in indoor cats was 26.0% as compared to 16.7% in outdoor cats. Other parasites identified included Ancylostoma spp. (10%; 4 cats), Toxocara cati (2%; 1 cat), Platynosomum spp. (22%; 9 cats), Mammomonogamus spp. (2%; 1 cat) and coccidia (7%; 3 cats). Conclusion: On St. Kitts, indoor cats are as likely to have parasite infections as outdoor cats. Given the zoonotic potential of some of the identified parasites, periodical anthelmintic treatment should be provided to both indoor and outdoor cats.